RANCANG BANGUN DAN ANALISIS PENGENALAN SAMPAH DALAM BENTUK ANIMASI 3D - Evaliata Br Sembiring; Mona Rai Situmorang (UNIVERSITAS PELITA HARAPAN, 2018)
Nowadays, the development of technology has reached almost all parts of life limitless. Its existence is used for solving the problems which often happen in daily life, for instance, the problem of trash. There are many programs to solve this problem but it does not enough because of the awareness the producer of trash. One of the best approaches is introducing trash and its influence on the early life of children by using 3D animation films. This product was developed by using Godfrey Method and analyzed based on the level of trash recognition by using color parameter, a form of object and duration. The result of this research: (1)3D animation film for introducing the variety of suitable trash to be used for learning media for children based on short duration to attract the children; (2)There are 4 categories and respondents to know more about the color based on clear and bright color. Keywords: Waste, 3D animation, Godfrey, Learning Media